A highly ordered multi-layered hydrogenated TiO2-II phase nanowire array negative electrode for 2.4 V aqueous asymmetric supercapacitors with high energy density and long cycle life. Issue 2 (15th December 2017) - Tang, Yongfu; Li, Yanshuai; Guo, Wenfeng; Wang, Jing; Li, Xiaomei; Chen, Shunji; Mu, Shichun; Zhao, Yufeng; Gao, Faming
Abstract : A highly ordered binderfree multi-layered hydrogenated TiO2 -II phase nanowire array (ML-HTO) negative electrode for 2.4 V aqueous asymmetric supercapacitors with high active materials loading, high electrical and ionic conductivity is synthesized via a multi-step method. Abstract : To increase the active material loading coupled with the improvement of electrical conductivity and ionic transport in the TiO2 based negative electrode for 2.4 V aqueous asymmetric supercapacitors (ASCs), a highly ordered binder-free multi-layered hydrogenated TiO2 -II phase nanowire array (ML-HTO) electrode is synthesized via a multi-step method. Due to the highly ordered scaffold-like multi-layered structure, a hydrogenated TiO2 -II phase, small TiO2 grains (4.4 nm), high oxygen vacancy (Ti 3+ ) concentration and functionalized hydrophilic surfaces, endowing the electrode with high electrical conductivity (low band gap of 2.39 eV), more positive flat-band potential (−0.35 V) and a high Na + diffusion coefficient (3.08 × 10 −8 cm 2 s −1 ), the as-prepared ML-HTO electrode with high active material loading (3.0 mg cm −2 ) exhibits a high areal specific capacitance (710.7 mF cm −2 ), which is much higher than that of a pristine TiO2 nanowire array (TO) electrode (28.3 mF cm −2 ) and the single layered hydrogenated TiO2 nanowire array (HTO) electrode (258.7 mF cm −2 ). Consequently, a 2.4 V aqueous ASC was firstly assembled with the ML-HTO electrode as the negative electrode, presenting a high energy density of 90.3 W h kg −1 at 349.0 W kg −1, as well as a high volumetric energy density of 9.6 mW h cm −3 at 61.0 mW cm −3, which is much higher than most of previously reported aqueous ASCs. The capacitance retention of the as-prepared MnO2 //ML-HTO ASC is 65.7% after 10 000 cycles, demonstrating its long cycle life.